The Effect of Gearing, Price Earning Ratio, Interest Rate, Risk on Abnormal Return - Muhammad Aldo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The purpose of the research is to analyze the effect of gearing, Price Earning Ratio (PER), interest rate, and risk on abnormal return. The research was conducted using secondary data. The sampling technique used was purposive sampling. The object of the research is to list companies on the Indonesia stock exchange from 2017-2020. The analysis method used is multiple linear regression analysis. By using regression analysis, the study provides evidence that all the independent variables such as gearing, Price Earning Ratio, and risk haven’t a significant positive effect on abnormal returns. Only one variable which is interest rate that has a significant positive effect on abnormal returns.